2012
DOI: 10.1177/0269215511432356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gait rehabilitation with a footpad-type locomotion interface in patients with chronic post-stroke hemiparesis: a pilot study

Abstract: This pilot study showed that gait rehabilitation using the GaitMaster4 was a feasible training method for chronic stroke patients. Calculation of the sample size indicated that a sample size of 38 participants would be adequate to test a null hypothesis of nil benefit additional to routine rehabilitation for chronic stroke patients in a future randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Some past reports have demonstrated electromechanical devices for gait rehabilitation, such as the Lokomat, 11 , 12) Gait Trainer, 13) and Gait Master. 14) These devices were developed to help patients in the swing phase, and control patient movements using a personal computer to assist them in moving their legs in a physiological gait pattern on a moving treadmill. Patients cannot influence the motion by themselves because these systems use a fixed gait pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Some past reports have demonstrated electromechanical devices for gait rehabilitation, such as the Lokomat, 11 , 12) Gait Trainer, 13) and Gait Master. 14) These devices were developed to help patients in the swing phase, and control patient movements using a personal computer to assist them in moving their legs in a physiological gait pattern on a moving treadmill. Patients cannot influence the motion by themselves because these systems use a fixed gait pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Gait Master 4 is another operational machine based on the movement of two footplates moved by a connecting rod-crank system. The footplates allow the movement of the human effector back and forth (to simulate the walk) or up and down (up/down the stairs) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the selective reporting domain, a proxy judgement was made that if a trial reported that a study protocol had been approved and the trial report described primary and secondary outcomes with results, then the trial could be considered at low risk of selective reporting bias. We classified RCTs as being at overall low risk of bias if they were rated as “low” for each of three key domains: (1) allocation concealment [ 31 ], (2) blinding of outcome assessment, and (3) completeness of outcome data. RCTs judged as being at high risk of bias for any of these domains were judged at overall high risk.…”
Section: Methodsmentioning
confidence: 99%